An Integrated Approach for Long Term Solutions of Flooding: A Study of the Eastern Chitwan Valley - Singh, Achyut Man (Hydro Nepal: Journal of Water, Energy and Environment, 2013)
A timeline study since 1976-2010 with satellite imagery maps on the flooding problems of Eastern Chitwan has revealed that due to the rapid degradation of the vegetative cover in the upper catchments of its rivers, increased flooding events had occurred. The conditions of the catchment environment depend on the behavior and activities of the people residing in the area. Infrastructure construction for the flood control in the river banks are short term solutions only effective for a few years. For a long term solution, the people of the area need to be sensitive for the river training works and good watershed management. The study has emphasized social and institutional aspect along with awareness campaign with the populations to achieve good impacts in the long term. Hydro Nepal; Journal of Water, Energy and Environment Vol. 12, 2013, January Page: 66-75 DOI: http://dx.doi.org/10.3126/hn.v12i0.9035 Uploaded Date : 10/29/2013